Organizational and Legal Aspects of Fee-based Education in the Republic of Kazakhstan - ALTYNBASOV, Bakhyt O.; MYRZATAYEV, Nurmukhamed; TASTEKEEV, Kairat; SAKTAGANOVA, Indira; OSMANOVA, Dinara (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017DO - 10.14505/jarle.v8.7(29).02, 2017)
The education system characteristics of the Republic of Kazakhstan were discussed and peculiarities of education on different levels were considered in this article. Advantages and disadvantages of fee-based education for the state and society were given. Comparative analysis of fee-based education development was made. The role of fee-based education in national human capital formation was examined. The state and society elite and human potential problems were researched. How to apply fee-based education in the current legislation and what negative sides of it exist – all these problems were reviewed in the article. Scientifically substantiated recommendations were made on the research results.